Respuesta :
Answer:
The answer to this question can be described as follows:
-5 with multiplicity 3
9 with multiplicity 2
-1 with multiplicity 1
Step-by-step explanation:
Given:
[tex]\Rightarrow f (x) = (x + 5)^3(x - 9)^2(x + 1)[/tex]
Solve the above equation:
[tex]\Rightarrow f (x) = (x + 5)(x + 5)(x + 5)(x - 9)(x - 9)(x + 1)\\[/tex]
The roots of the polynomial are as follows:
[tex]\Rightarrow (x-x_1)(x-x_2)(x-x_3)......(x-x_n)\\\\\Rightarrow x_1,x_2,x_3.........x_n[/tex]
That's why the roots are:
5 with multiplicity 3
9 with multiplicity 2
-1 with multiplicity 1
Answer:
answer:
a. -5 with multiplicity 3
d. 9 with multiplicity 2
f. -1 with multiplicity 1
Step-by-step explanation: